The effects of valence and perceived brand globalness on trust in eWOM and on eWOM’s influence - Algur, Mehmet Selami. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
Word of mouth’s effect on consumer behavior is already known. Developments in internet and mobile technologies have created a new form of this phenomenon, electronic word of mouth. It is not only capable to reach higher number of people, it is also able to reach them in much less time. That is why it is important to understand electronic word of mouth’s dynamics. The aim of this study is to undertand how perceived brand globalness and valence effects turstworthiness and influence of electronic word of mouth. Data have been collected from 160 electronic word of mouth users and have been analyzed by using correlation, regression, multiple regression, T-Tests and ANOVA. Results of analysis determine perceived brand globalness negatively effects trustworthiness and influence of positıve electronic word of mouth, and positıvely effects trustworthiness and influence of negative electronic word of mouth. Besides, this study shows the relationship between demographics, purchase intention, perceived quality and perceived brand globalness, as well as the effect of valence.
Keywords: Word-of-mouth advertising.